Self-shading in cork oak seedlings: Functional implications in heterogeneous light environments - Esteso-Martínez, Jordán; Peguero-Pina, José Javier; Valladares, Fernando; Morales, Fermín; Gil-Pelegrín, Eustaquio (Acta Oecologica, 2010)
The high self-shading found in Quercus suber seedlings has been interpreted as a feature common for plants growing in high light environments. But many studies reveal that Q. suber has high survival rates under low-light conditions, so a high degree of self-shading could be the consequence of a foliage composed of many small leaves, with no drawbacks for coping with low light. A characterization of the light environment in a Q. suber stand together with a study of photosynthetic parameters of full sunlightexposed (FSLE) and self-shaded (SS) leaves were carried out to tackle this apparent contradiction. Although the number of sunﬂecks longer than 120 min during the 3 months of measurements was low, the occurrence of at least one sunﬂeck longer than 120 min per day in the understory of the forest studied was very common. Sunﬂecks shorter than 30 min promoted an increase in net photosynthesis (A) in FSLE leaves, but not in SS leaves. However, sunﬂecks longer than 60 min led to a very strong decrease in A and in actual photosystem II efﬁciency (FPSII ) in FSLE leaves, when compared to sunﬂecks shorter than 30 min. In SS leaves, changes were, again, negligible. The multi-layered foliage of Q. suber seedlings allowed i) FSLE leaves to obtain the maximum photosynthetic yield for short sunﬂecks, and ii) SS leaves to increase their contribution to the photosynthesis of the whole plant for long sunﬂecks, thus, optimizing the use of light by FSLE and SS leaves during short and long sunﬂecks respectively. Therefore, shoot architecture of Q. suber seedlings involving high levels of self-shading allows to adequately cope with the low but highly heterogeneous light conditions of the understory, particularly when sunﬂecks of contrasting durations take place as it is frequently the case for evergreen Mediterranean forests
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: Canopy structure; Light stress; Mediterranean; Quercus suber; Self-shading

Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis

Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis